Diversity Analysis of Endophytic Fungi Isolated from Millettia utilis Dunn (Leguminosae-Papilionoideae) and Screening for Antibacterial Activity - Sutjaritvorakul, Thanawat (Journal of Advanced Development in Engineering and Science, 2023)
Endophytic fungi were isolated from healthy leaves of medicinal plant (Millettia utilis Dunn). Fourteen fungal endophytes representing different morphotaxa were characterized from 40 cultures. Aspergillus sp. I, Phyllosticta spp. and Pestalotiopsis spp. show the highest percentage of colonization frequency (CF %). All endophytic fungal isolates were tested for antibacterial activity against gram positive and negative pathogenic bacteria such as Bacillus subtilis, Staplyococus aureus, Escherichia coli and Pseudomonas aerogenosa by the paper disk susceptibility test. Crud extract inhibited the growth of gram positive bacteria more than gram negative bacteria. Xylaria spp. showed the highest broad spectrum of antibacterial activity against all test microorganisms.